Exploring curcumin and rosmarinic acid as potential antidotes for pesticide-induced harm to honey bees - Mohamadzade Namin, Saeed; Begna, Tekalign; Kang, Youngrak; Bisrat, Daniel; Najarpoor, Arezoo; Ulziibayar, Delgermaa; Vatanparast, Mohammad; Jung, Chuleui (Frontiers in Insect Science, 2025)
Honey bees are essential pollinators in global food production, however, their populations are increasingly threatened by insecticides. Protecting bees from these chemical stressors is critical not only for ecosystem stability but also for agricultural sustainability. Natural dietary compounds, such as curcumin (CU) and rosmarinic acid (RA), have demonstrated antioxidant and detoxification-promoting properties in other organisms and may offer a promising approach to enhancing honey bee resilience to pesticide exposure. This study investigates the potential of CU and RA to mitigate pesticide-induced harm in honey bees. In acute toxicity tests, newly emerged bees and foragers were topically exposed to lethal doses of acetamiprid (1.04 µg/bee for newly emerged and 15.3 µg/bee for forager), carbaryl (0.06 µg/bee for newly emerged and 0.51 µg/bee for forager), and flupyradifurone (15.6 µg/bee for newly emerged and 24.1 µg/bee for forager), followed by post-feeding with CU and RA at 50, 100, and 200 ppm for 48h. Additionally, the effects of CU and RA at 100 ppm were tested under chronic oral intoxication through continuous insecticide feeding. CU100 significantly reduced mortality in insecticide-exposed bees, except foragers exposed to acetamiprid, while RA showed variable detoxification effects, with RA100 and RA200 improving survival in carbaryl-exposed bees and RA50 enhancing survival of 0.06 µg/bee for newly emerged bees exposed to flupyradifurone. Chronic toxicity assessments confirmed CU100’s superior protective effect over RA100, especially in carbaryl-exposed groups. Gene expression analysis revealed that CU and RA modulated detoxification related genes, enhancing honey bees' resilience by upregulating key detoxification genes in the head and abdomen. These findings suggest that CU and RA offer potential benefits in reducing insecticide toxicity in honey bees. However, further research is needed to assess their effects across different life stages, environmental conditions, and colony dynamics, as well as to elucidate the pathways involved in detoxification gene regulation. A comprehensive understanding of their mechanisms and ecological implications is essential before considering these compounds for practical applications in pollinator health management.